ПОСТРОЕНИЕ СОБСТВЕННЫХ ФУНКЦИЙ ЗАДАЧИ ФРАНКЛЯ ДЛЯ УРАВНЕНИЯ СМЕШАННОГО ТИПА С ТРЕМЯ СИНГУЛЯРНЫМИ КОЭФФИЦИЕНТАМИ (Scientific journal of the Fergana State University, 2023)
In this paper the method of separation of the variables is used to construct the eigenfunctions of the Frankl problem for a three-dimensional equation of mixed type with three singular coefficients.